Evaluation of an implemented new insulin chart to improve quality and safety of diabetes care in a large university hospital: a follow-up study. Issue 1 (26th January 2021) - Kopanz, Julia; Sendlhofer, Gerald; Lichtenegger, Katharina; Semlitsch, Barbara; Riedl, Regina; Pieber, Thomas R; Tax, Christa; Brunner, Gernot; Plank, Johannes
Abstract : Objectives: To evaluate structure, documentation, treatment quality of a new implemented standardised insulin chart in adult medical inpatient wards at a university hospital. Design: A before–after study (3 to 5 months after implementation) was used to compare the quality of old versus new insulin charts. Setting: University Hospital Graz, Austria. Participants: Healthcare professionals (n=237) were questioned regarding structure quality of blank insulin charts. Interventions: A new standardised insulin chart was implemented and healthcare professionals were trained regarding features of this chart. Data from insulinised inpatients were evaluated regarding documentation and treatment quality of filled-in insulin charts (n=108 old insulin charts vs n=100 new insulin charts). Main outcomes and measures: The primary endpoint was documentation error for insulin administration. Results: Healthcare professionals reported an improved structure quality of the new insulin chart with a Likert type response scale increase in all nine items. Documentation errors for insulin administration (primary endpoint) occurred more often on old than new insulin charts (77% vs 5%, p<0.001). Documentation errors for insulin prescription were more frequent on old insulin charts (100% vs 42%) whereas documentation errors for insulin management rarely occurred in any group (10% vs 8%). Patients of both chart evaluation groups (age: 71±11 vs 71±12 years, 47% vs 42% women, 75% vs 87% type 2 diabetes for old vs new charts, respectively) had a mean of 4±2 good diabetes days. Overall, 26 vs 18 hypoglycaemic episodes (blood glucose (BG) <4.0 mmol/L (72 mg/dL), p=0.28), including 7 vs 2 severe hypoglycaemic episodes (BG <3.0 mmol/L (54 mg/dL), p=0.17) were documented on old versus new insulin charts. Conclusions: The implementation of a structured documentation form together with training measures for healthcare professionals led to less documentation errors and safe management of glycaemic control in hospitalised patients in a short time follow-up. A rollout at further medical wards is recommended, and sustainability in the long-term has to be demonstrated.